1985
DOI: 10.1126/science.2412294
|View full text |Cite
|
Sign up to set email alerts
|

Differential Control of U1 Small Nuclear RNA Expression During Mouse Development

Abstract: During normal mouse development the relative amounts of two types of U1 small nuclear RNA's (U1 RNA) change significantly. Fetal tissues have comparable levels of the two major types of mouse U1 RNA's, mU1a and mU1b, whereas most differentiated adult tissues contain only mU1a RNA's. Those adult tissues that also accumulate detectable amounts of embryonic (mU1b) RNA's (for example, testis, spleen, and thymus) contain a significant proportion of stem cells capable of further differentiation. Several strains of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 28 publications
(11 reference statements)
4
87
0
Order By: Relevance
“…Measurements of the signal intensities showed that Ul snRNA is -500 times more abundant than U7 RNA in C127 cells, whereas in K21 cells this difference is only 60-fold. Since K21 cells, but not C 127, additionally express the embryonic Ulb RNA at 5-to 10-fold higher levels than U7 RNA (Figure 2;Lund et al, 1985) the overall difference in K21 cells is -65-to 70-fold.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements of the signal intensities showed that Ul snRNA is -500 times more abundant than U7 RNA in C127 cells, whereas in K21 cells this difference is only 60-fold. Since K21 cells, but not C 127, additionally express the embryonic Ulb RNA at 5-to 10-fold higher levels than U7 RNA (Figure 2;Lund et al, 1985) the overall difference in K21 cells is -65-to 70-fold.…”
Section: Resultsmentioning
confidence: 99%
“…For analyses of U4 RNAs, we used partially denaturing gels [containing 12% (30:0.8)polyacrylamide, 7 M urea and 1 x TEB; Lund et al 1985] which were found to resolve at least six different forms of xU4 RNAs.…”
Section: Isolation Of Unlabeled Rnas For Northern Blot Analysesmentioning
confidence: 99%
“…erences therein), we and others have proposed that differential expression of snRNA genes during development might be responsible, in part, for selection of alternative splice sites during pre-mRNA processing Lund et al 1985;Laski et al 1986). …”
mentioning
confidence: 99%
“…There is developmentally regulated expression of the mouse Ul Nucleic Acids Research RNAs as well (12). The Ulb RNAs are expressed in early mouse development and in many tumor lines but not in many terminally differentiated cells (12) or in fibroblasts (13).…”
Section: Introductionmentioning
confidence: 99%